To identify the ordered pair of the endpoint in the standard form of the square root function \( y = 5\sqrt{x - 4} - 1 \), we first need to analyze the function and rewrite it in the standard form of a square root function, which is generally expressed as \( y = a\sqrt{x - h} + k \).
From the equation:
- We can observe that \( a = 5 \),
- The expression under the square root is \( x - 4 \), indicating that \( h = 4 \),
- The constant term outside the square root is \( -1 \), indicating that \( k = -1 \).
The standard form tells us that the vertex (or endpoint) of the square root function is given by the ordered pair \( (h, k) \).
Thus, in this case:
- \( h = 4 \)
- \( k = -1 \)
Therefore, the ordered pair of the endpoint is \( (4, -1) \).
The correct response is:
(4,−1) left parenthesis h comma k right parenthesis